2018
DOI: 10.1016/j.celrep.2018.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Specific Menin Deletion Leads to Synaptic Dysfunction and Cognitive Impairment by Modulating p35 Expression

Abstract: Menin (MEN1) is a critical modulator of tissue development and maintenance. As such, MEN1 mutations are associated with multiple endocrine neoplasia type 1 (MEN1) syndrome. Although menin is abundantly expressed in the nervous system, little is known with regard to its function in the adult brain. Here, we demonstrate that neuron-specific deletion of Men1 (CcKO) affects dendritic branching and spine formation, resulting in defects in synaptic function, learning, and memory. Furthermore, we find that menin bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…To investigate potential astrocyte-or neuron-specific effects associated with depressive-like phenotypes derived from Men1 gene deletion, we generated CNS-specific whole-brain (NcKO), neuron-specific (CcKO), and GcKO Men1 deletion mouse lines by crossing the floxed Men1 allele with Nestin-Cre, CamkIIa-cre, or GFAP-Cre transgenic lines (Akbarian et al, 2002;Scacheri et al, 2004;Tronche et al, 1999;Trumpp et al, 1999;Westerman et al, 2012), respectively ( Figure 2A). Global Men1 deletion in the CNS resulted in early postnatal lethality (Zhuang et al, 2018); therefore, we used heterozygous Men1 deletion strains generated by Nestin-Cre crosses (Nestin-Cre, Men1 f/+ ) for comparison. Men1 CcKO and GcKO animals exhibited normal growth rate; body and brain sizes, in addition to longevity, were indistinguishable from Ctrls (Men1 f/f animals were used as Ctrls) ( Figures S3A-S3C) (Zhuang et al, 2018).…”
Section: Generation Of Men1 Brain Cell-type-specific Conditional Knocmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate potential astrocyte-or neuron-specific effects associated with depressive-like phenotypes derived from Men1 gene deletion, we generated CNS-specific whole-brain (NcKO), neuron-specific (CcKO), and GcKO Men1 deletion mouse lines by crossing the floxed Men1 allele with Nestin-Cre, CamkIIa-cre, or GFAP-Cre transgenic lines (Akbarian et al, 2002;Scacheri et al, 2004;Tronche et al, 1999;Trumpp et al, 1999;Westerman et al, 2012), respectively ( Figure 2A). Global Men1 deletion in the CNS resulted in early postnatal lethality (Zhuang et al, 2018); therefore, we used heterozygous Men1 deletion strains generated by Nestin-Cre crosses (Nestin-Cre, Men1 f/+ ) for comparison. Men1 CcKO and GcKO animals exhibited normal growth rate; body and brain sizes, in addition to longevity, were indistinguishable from Ctrls (Men1 f/f animals were used as Ctrls) ( Figures S3A-S3C) (Zhuang et al, 2018).…”
Section: Generation Of Men1 Brain Cell-type-specific Conditional Knocmentioning
confidence: 99%
“…Global Men1 deletion in the CNS resulted in early postnatal lethality (Zhuang et al, 2018); therefore, we used heterozygous Men1 deletion strains generated by Nestin-Cre crosses (Nestin-Cre, Men1 f/+ ) for comparison. Men1 CcKO and GcKO animals exhibited normal growth rate; body and brain sizes, in addition to longevity, were indistinguishable from Ctrls (Men1 f/f animals were used as Ctrls) ( Figures S3A-S3C) (Zhuang et al, 2018). To confirm astrocyte-specific menin reduction in GcKO transgenic animals, we performed menin/glial fibrillary acidic protein (GFAP) and menin/NeuN double staining in GcKO brain cortex.…”
Section: Generation Of Men1 Brain Cell-type-specific Conditional Knocmentioning
confidence: 99%
“…In recent years, numerous publications on the relation between AD and the gut microbiota have also become available ( Table 1 ) . Metagenomic techniques have proved different taxonomic levels in the microbiota composition of the Alzheimer’s patients compared to healthy controls or elderly without dementia [ 87 , 88 ]. However, until now, few studies supported in vivo a causative effect between gut dysbiosis and neurobehavioral abnormalities.…”
Section: Oral and Gut Microbiota In Alzheimer’s Diseasementioning
confidence: 99%
“…For instance, multiple endocrine neoplasia type 1 ( MEN1 )—a tumor suppressor gene, which is mutated in patients with MEN1 syndrome [ 1 ]—is expressed in almost all developing tissues and organs [ 2 ]. MEN1 knockout generates a lethal phenotype, thus making it difficult to decipher its precise function in the intact animal [ 3 ]. Moreover, MEN1 orthologues have been found in Drosophila [ 4 ], Lymnaea [ 5 ], rodents [ 6 ], etc., demonstrating that functionally this gene is evolutionarily highly conserved.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations into menin’s crystal structure and its physiological aspect of crosstalk in myriad signaling pathways [ 7 ] have shed some further light onto its role in gene expression and cell–cell signaling involved in various important cellular pathways [ 8 ]. It is interesting to note that although menin expression in the brain is the highest during development, it does nevertheless become restricted to only cortical and hippocampal regions in the adult CNS, suggesting a potential role in regulation of neurite growth, synapse formation, synaptic plasticity [ 9 ], learning, memory and cognition [ 3 ] in a host of animal models. Consistent with this postulate, recent studies [ 10 ] have identified a homologue of MEN1 gene in the mollusc Lymnaea (L-menin), which was differentially expressed in postsynaptic neurons exhibiting cholinergic phenotype.…”
Section: Introductionmentioning
confidence: 99%